2012
DOI: 10.1177/875512251202800405
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Medication Complexity in Community-Living Older Adults: The Health, Aging and Body Composition Study

Abstract: Background Medication complexity is a large determinant of adherence. Few studies have explored the relationship between cognitive impairment and medication complexity. Objective To evaluate whether cognitive impairment is associated with medication complexity for prescription and over-the-counter (OTC) medications. Methods In this cross-sectional analysis, we studied the association between cognitive impairment and the complexity of prescription and OTC drug regimens. Baseline participants were from the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…This was consistent with a previous study conducted in 3055 older adults that found that participants with cognitive impairment had lower regimen complexity [42]. The authors of this study suggested that prescribers might have simplified medication regimens to facilitate easier medication management in people with cognitive impairment.…”
Section: Discussionsupporting
confidence: 91%
“…This was consistent with a previous study conducted in 3055 older adults that found that participants with cognitive impairment had lower regimen complexity [42]. The authors of this study suggested that prescribers might have simplified medication regimens to facilitate easier medication management in people with cognitive impairment.…”
Section: Discussionsupporting
confidence: 91%
“…However, our finding of higher persistence in very elderly patients with dementia contrasts with the results from several previous studies reporting a higher discontinuation rate for antihypertensive treatment among patients with dementia or cognitive impairment [ 27 , 28 ]. These contradictory findings are somewhat puzzling, and may be partially explained by the lower medication complexity in older adults with cognitive impairment, as observed in one previous study [ 29 ]. The care management by caregivers may also increase the treatment persistence in the very elderly with dementia [ 30 ], which is supported by the findings of recent studies that dementia was associated with the likelihoods of continuing statin therapy (aHR, 0.84; 95% CI, 0.73–0.98) and antiplatelet therapy in elderly patients after ischemic stroke [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 84%
“…Our study found an inverse association between medication regimen complexity and dementia severity in multivariate analysis. Previous studies have reported residents with cognitive impairment are less likely to have complex medication regimens,40,47,48 and are less likely to experience polypharmacy, or the concomitant use of multiple medications (commonly >8) 2,49. Recently, there has been focus in Australia on implementing a palliative approach to medication prescribing for residents with advanced dementia, and deprescribing for all older adults experiencing inappropriate polypharmacy 50,51.…”
Section: Discussionmentioning
confidence: 99%